“Hot Zones” for Otolaryngologists: Assessing the geographic distribution of aerosol-generating procedures amidst the COVID-19 pandemic - Quereshy, Humzah A.; Jella, Tarun K.; Ruthberg, Jeremy S.; Kocharyan, Armine; D'Anza, Brian; Maronian, Nicole; Otteson, Todd D. (American journal of otolaryngology, 2020)
Given high COVID-19 viral load and aerosolization in the head and neck, otolaryngologists are subject to uniquely elevated viral exposure in most of their inpatient and outpatient procedures and interventions. While elective activity has halted across the board nationally, the slow plateau of COVID-19 case rates prompts the question of timing of resumption of clinical activity. We sought to prospectively predict geographical “hot zones” for otolaryngological exposure to COVID-19 based on procedural volumes data from 2013 to 2017. Otolaryngologic CPT codes were stratified based on risk-level, according to recently published specialty-specific guidelines. Using the Medicare POSPUF database, aerosol-generating procedures (AGPs) were mapped based on hospital referral regions, against up-to-date COVID-19 case distribution data, as of April 24, 2020. The most common AGPs were diagnostic flexible laryngoscopy, diagnostic nasal endoscopy, and flexible laryngoscopy with stroboscopy. The regions with the most AGPs per otolaryngologist were Iowa City, IA, Detroit, MI, and Burlington, VT, while the states with the most COVID-19 cases as of April 24th are New York, New Jersey, and Massachusetts. Our study provides a model for predicting possible “hot zones” for otolaryngologic exposure based on both COVID-19 case density and AGP-density. As the focus shifts to resuming elective procedures, these potential “hot zones” need to be evaluated for appropriate risk-based decision-making, such as “reopening strategies” and allocation of resources.